Pengaruh Karakteristik Influencer Pada Keputusan Beli Berdasarkan Model Adopsi Informasi - Triwibowo, Renaldi; Astuti, Budi (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This study aims to examine the impact of influencer characteristics, specifically attractiveness, trustworthiness, expertise, and popularity on purchasing decisions for Scarlett beauty products. The research employs a quantitative approach by distributing questionnaires online to 214 respondents who are familiar with the Scarlett brand and know JKT48 as a celebrity. The collected data were analyzed using SmartPLS software with the PLS-SEM method. Based on the result, it is known that attractiveness and trustworthiness have a significant effect on purchase intention. However, expertise and popularity do not significantly influence purchase intention. This study also reveals that purchase intention significantly affects purchasing decisions